A review of invasive intracranial pressure monitoring following surgery for hypertensive cerebral hemorrhage - Chen, Fu; Zhang, Shukui; Li, Bingzhen; Zhang, Jin; Ran, Maoxin; Qi, Bin (Frontiers in Neurology, 2023)
Hypertensive cerebral hemorrhage, the most common type of spontaneous cerebral hemorrhage, has a high mortality and disability rate and limited therapeutic options for patients' prognostic function, making the disease a burden not only for patients' families but also a great challenge for national health care systems. The rise in intracranial pressure following hypertensive cerebral hemorrhage is one of the most important causes of death, but the rise in intracranial pressure precedes the onset of clinical symptoms and signs, and the early onset of clinical symptoms and signs is often atypical, so treatment may be delayed until the onset of typical symptoms and signs, with irreversible consequences for the patient. Therefore, early capture of intracranial pressure changes for timely, effective and targeted treatment will reduce patient mortality. Invasive intracranial pressure monitoring provides real-time dynamic and accurate monitoring of changes in intracranial pressure in patients, providing clinicians with therapeutic guidance and effectively addressing the limitations of relying solely on empirical treatment. This article reviews the use of invasive intracranial pressure in postoperative hypertensive cerebral hemorrhage, hoping to bring help to clinical and scientific research.